2019
DOI: 10.1016/j.jmii.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients with low lactate level and septic shock

Abstract: Arterial lactate is a very reliable diagnostic and prognostic predictor of septic shock. However, despite low arterial lactate, patients with a high APACHEⅡ score, high C-reactive protein levels, and chronic heart failure had a poorer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
3
16
0
2
Order By: Relevance
“…However, although initial elevated lactate was an independent risk factor for mortality, its predictive value was not sufficient in our study. Conversely, Oh et al suggested that despite low arterial lactate, patients with a high APACHE II score, had a poorer prognosis [ 37 ]. Although lactate levels were intravenously tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, although initial elevated lactate was an independent risk factor for mortality, its predictive value was not sufficient in our study. Conversely, Oh et al suggested that despite low arterial lactate, patients with a high APACHE II score, had a poorer prognosis [ 37 ]. Although lactate levels were intravenously tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Serum lactate was identi ed as another risk factor associated with in-hospital death in our study. Lactate has been used as a prognostic marker in predicting the severity and outcome of sepsis and septic shock [25]. Shankar-Hari et al suggested in their study that the adjusted odds ratio for hospital mortality increased linearly with lactate levels with lactate level > 2 mmol/L being the cutoff value for the diagnosis of septic shock [26].…”
Section: Discussionmentioning
confidence: 99%
“…Serum lactate was identi ed as another risk factor associated with in-hospital death in our study. Lactate has been used as a prognostic marker in predicting the severity and outcome of sepsis and septic shock [28]. Shankar-Hari et al suggested in their study that the adjusted odds ratio for hospital mortality increased linearly with increasing lactate levels with lactate level > 2 mmol/L being the cutoff value for the diagnosis of septic shock [29].…”
Section: Discussionmentioning
confidence: 99%